Khipu, Llautu: una familia de textos textiles - Fossa, Lydia (2019)
Textile art style patterns belonging to a unique ethnic group express specific information. They may be present in khipu configuration, since it is also a textile. Khipu would thus belong to the textile objects family of a given human group. Specific style khipu configuration could be considered an identity sign of a given ethnic group, which I propose in this article. The association of each archaeological khipu to a specific ethnic group and, within it, to a level of indigenous administration, is plausible.